2008
DOI: 10.1007/s10238-008-0016-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of methylprednisolone on treatment in rats with induced sepsis

Abstract: In this study, an appropriate sepsis model was created in rats. Additionally, the effects of steroid treatments on survival, in connection with antibiotic treatment, were investigated. The sepsis model performed via intraperitoneal injection of 3 ml/kg fecal suspension was determined as the most appropriate model for our study. Fifteen rats were used to investigate the effect of piperacillin-tazobactam on sepsis treatment. Forty-five randomly selected rats were used to investigate the efficacy of the antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In addition, animal studies have repeatedly demonstrated that exogenous corticosteroids can impair host neutrophil-mediated bacterial clearance mechanisms [79], which might explain the excess of positive blood cultures we observed in DOC + DEX-treated animals. More specific to our own study, corticosteroid therapy has been shown to decrease bacterial clearance from the lung in murine models [8], and is most efficacious when administered with appropriate antibiotic therapy [2628]. These data suggest that adequately dosed and appropriately selected antibiotic therapy is essential whenever corticosteroids are used in septic shock.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, animal studies have repeatedly demonstrated that exogenous corticosteroids can impair host neutrophil-mediated bacterial clearance mechanisms [79], which might explain the excess of positive blood cultures we observed in DOC + DEX-treated animals. More specific to our own study, corticosteroid therapy has been shown to decrease bacterial clearance from the lung in murine models [8], and is most efficacious when administered with appropriate antibiotic therapy [2628]. These data suggest that adequately dosed and appropriately selected antibiotic therapy is essential whenever corticosteroids are used in septic shock.…”
Section: Discussionmentioning
confidence: 94%
“…However, it suffers from such limitations as the high variability among researchers ( 18 ) and the difficulty in making comparisons among animals with different cecum shapes and sizes ( 4 ). Another known model of sepsis using fecal suspensions has been reported in mice ( 4 ), rats ( 11 ), and sheep ( 12 , 13 ). However, its position as a sepsis model is not well established because their preparation methods are not clearly described ( 11 ) or are complicated ( 4 , 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another known model of sepsis using fecal suspensions has been reported in mice ( 4 ), rats ( 11 ), and sheep ( 12 , 13 ). However, its position as a sepsis model is not well established because their preparation methods are not clearly described ( 11 ) or are complicated ( 4 , 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%